Sodium supplement additive, positive pole piece and sodium ion battery

By using sodium supplement additives of Na2C2O4 and NaNO2 in sodium ion batteries, the decomposition potential of organic sodium supplement agents is reduced by oxidizing gas, the problem of sodium ion consumption during the first charging and discharging of sodium ion batteries is solved, and the energy density and cycle life of the battery are improved.

CN120072938APending Publication Date: 2025-05-30NANKAI UNIV

Patent Information

Application Number
CN202510217500.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-05-30

AI Technical Summary

Technical Problem

The sodium ion battery is irreversibly consumed during the first charge and discharge process, resulting in low energy density and poor cycle life.

Method used

Using sodium supplement additives including organic sodium supplement Na2C2O4 and gas-generating sodium salt NaNO2, an oxidative decomposition of inorganic additives at low potentials is used to generate oxidative gas, react with organic sodium supplement agents, reduce the decomposition potential and achieve sodium compensation.

Benefits of technology

It significantly reduces the decomposition potential of the organic sodium supplement agent, improves the first Coulomb efficiency, avoids the decline in the utilization rate of the positive electrode material, simplifies the process flow, and improves the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120072938A_ABST
    Figure CN120072938A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium pre-treatment of sodium ion batteries, and discloses a sodium supplementing additive, a positive pole piece and a sodium ion battery. The sodium supplementing additive comprises an organic sodium supplementing agent and an inorganic additive, the inorganic additive is gas-generating sodium salt, and a gas product obtained by oxygenolysis of the gas-generating sodium salt under a certain potential has oxidability and can effectively oxidize decomposition of the organic sodium supplementing agent so as to realize sodium compensation. On one hand, the inorganic additive has reversibility in the reaction process, a small amount of additive can realize decomposition of a large amount of organic sodium supplement, and the influence of excessive additive and product thereof on a positive electrode material and even a battery system is avoided; on the other hand, the gas oxidizing agent can be in full contact with the organic sodium supplementing agent, the decomposition potential of the organic sodium supplementing agent is remarkably reduced, the first coulombic efficiency is effectively improved, and wide research prospects and application values are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium-ion batteries, and particularly relates to a sodium supplement additive, a positive electrode sheet, and a sodium-ion battery. Background Art

[0002] With the rapid development of renewable energy and the increasing demand for electric vehicles, sodium-ion batteries have become a potential battery technology attracting much attention due to their advantages such as rich raw materials, low cost, and environmental friendliness. At present, significant progress has been made in the development of electrode materials and electrolytes for sodium-ion full batteries. However, it still faces some key problems in practical applications, such as low energy density and poor cycle life. The main reason is that sodium ions are irreversibly consumed during the first charge-discharge process. Specifically, this loss mainly stems from the reduction and decomposition of the electrolyte on the surface of the negative electrode to form a solid electrolyte interface (SEI) film, accompanied by the irreversible consumption of sodium ions.

[0003] To solve these problems, the sodium compensation strategy has received extensive attention due to its simple operation and easy expansion. There are mainly two existing technologies: one is to add an excessive amount of sodium ions to the positive electrode material to make up for the sodium loss, but this method will lead to a decrease in the utilization rate of the positive electrode material, thereby affecting the overall energy density of the battery; the other is to use the pre-sodiation technology for the negative or positive electrode material, and compensate for the irreversible capacity loss generated during the first charge-discharge process by adding extra sodium in advance. Among them, the positive electrode self-sacrificing additive has shown good application prospects in large-scale production due to its advantages such as low cost, simple process, and high safety, and thus has been widely studied.

[0004] There are various types of positive electrode additives, which can generally be divided into two categories: inorganic and organic. Compared with inorganic additives, organic additives have a higher sodium compensation capacity, and neither they nor their oxidation products have an impact on the subsequent cycles of the battery. However, the organic additives have poor conductivity, resulting in a higher decomposition potential, which may cause problems such as incompatibility with the positive electrode material and decomposition of the electrolyte at high voltages. At present, the main solution strategies include reducing the particle size, compounding with carbon materials, and adding metal catalysts, etc., but these methods often have problems such as poor effect, complex processes, or the generation of harmful residues. Therefore, developing a method that can effectively reduce the decomposition potential of the sodium supplement agent for the positive electrode material has become the key to improving the performance of sodium-ion batteries and ensuring battery safety. Summary of the Invention

[0005] The purpose of the present invention is to solve the problem of low initial Coulombic efficiency of sodium-ion full batteries, and provide a sodium supplement additive, a positive electrode sheet, and a sodium-ion battery. The oxidizing gas generated by the low-potential decomposition of the used inorganic additive can be in full contact with the organic sodium supplement agent, improving the decomposition efficiency of the organic sodium supplement agent and reducing the decomposition potential of the organic sodium supplement agent.

[0006] For the above purposes, the technical solution of the present invention is as follows:

[0007] The first aspect of the present invention provides a sodium supplement additive, comprising: an organic sodium supplement agent and an inorganic additive, wherein the inorganic additive is a gas-generating sodium salt, and the gas product generated by the oxidation and decomposition of the gas-generating sodium salt at a certain potential has oxidizing properties and can oxidize and decompose the organic sodium supplement agent to achieve sodium compensation.

[0008] Further, the organic sodium supplement agent is Na 2 C 2 O 4 and the gas-generating sodium salt is NaNO 2 . The oxidation and decomposition potential of the gas-generating sodium salt is 3.0 - 3.5V, and the decomposition product is an oxidizing gas NO 2 .

[0009] The specific reaction process is as follows:

[0010]

[0011] The second aspect of the present invention provides a positive electrode sheet, which comprises the above sodium supplement additive, a conductive agent and a binder.

[0012] The specific preparation method is as follows: Dissolve the sodium supplement additive, the conductive agent and the binder in a solvent, stir evenly under vacuum to obtain a positive electrode slurry, evenly coat the positive electrode slurry on an aluminum foil current collector, and dry it at 70°C - 90°C under vacuum to obtain the positive electrode sheet.

[0013] Further, the mass ratio of the sodium supplement additive, the conductive agent and the binder is 40 - 50:30 - 40:10 - 20.

[0014] Further, the positive electrode sheet further comprises a positive electrode active material. The positive electrode active material is at least one of transition metal layered oxides, tunnel phase oxides, polyanion compounds, etc. The mass ratio of the positive electrode active material, the sodium supplement additive, the conductive agent and the binder is 65 - 75:5 - 15:10 - 15:10 - 15, the organic sodium supplement agent accounts for 3 - 6% of the mass of the positive electrode slurry, and the inorganic additive accounts for 2 - 5% of the mass of the positive electrode slurry.

[0015] The specific preparation method is as follows: Dissolve the positive electrode active material, the sodium supplement additive, the conductive agent and the binder in a solvent, stir evenly under vacuum to obtain a positive electrode slurry, evenly coat the positive electrode slurry on an aluminum foil current collector, and dry it at 70°C - 90°C under vacuum to obtain the positive electrode sheet.

[0016] Further, the conductive agent is Super P, the binder is PVDF, and the solvent is NMP.

[0017] The third aspect of the present invention is to provide a sodium-ion battery, including the above-mentioned positive electrode sheet. The specific operation is as follows: Assemble the positive electrode sheet, separator, electrolyte, and negative electrode sheet in a glove box atmosphere, and finally obtain a sodium-ion battery.

[0018] Preferably, the electrolyte solute is 1M NaPF 6 , the solvent is EMC, EC and DMC, and the volume ratio of EMC, EC and DMC is 1:1:1. The separator is Glass fiber. The negative electrode sheet is at least one of a sodium metal sheet and hard carbon.

[0019] The fourth aspect of the present invention is to provide the application of the sodium supplement additive in a sodium-ion battery.

[0020] Advantages and beneficial effects of the present invention:

[0021] 1. The NaNO 2 additive selected in the present invention decomposes at a low potential to generate an oxidizing NO 2 gas, which reacts with Na 2 C 2 O 4 to reduce the decomposition potential and achieve sodium compensation. In this process, the NaNO 2 additive is reversible, and only a small amount of additive is required to decompose a large amount of sodium oxalate, avoiding the influence of excessive additives and their products on the positive electrode material and even the battery system.

[0022] 2. The oxidizing gas selected in the present invention can be in full contact with the organic sodium supplement agent, significantly reducing the decomposition potential of the organic sodium supplement agent and accelerating the release of Na + in the organic sodium supplement agent, effectively improving the first Coulombic efficiency.

[0023] 3. When the sodium supplement additive of the present invention is used, it is directly added during the stirring of the positive electrode, and it can be compatible with the existing homogenization coating process. This method has simple operation, short process flow, rapid reaction, high safety, and is very easy to industrialize. Description of the Drawings

[0024] Figure 1 is the first-cycle charge-discharge curve of the positive electrode sheet half-cell prepared in Example 1 and Comparative Example 1;

[0025] Figure 2 is the first-cycle charge-discharge curve of the positive electrode sheet half-cell prepared in Example 2 and Comparative Example 2;

[0026] Figure 3 is the first-cycle charge-discharge curve of the positive electrode sheet full-cell prepared in Example 3 and Comparative Example 3;

[0027] Figure 4It is the first charge-discharge curve of the full cell of the positive electrode sheet prepared in Comparative Example 4;

[0028] Figure 5 It is the first charge-discharge curve of the full cell of the positive electrode sheet prepared in Comparative Example 5. Specific Embodiments

[0029] The present invention will be described in detail and completely below in conjunction with the accompanying drawings, but these embodiments do not mean to limit the protection scope of the present invention. The reagents used in the embodiments are all commercially available or obtained through conventional synthesis methods in the art without special instructions.

[0030] Example 1

[0031] Mix the organic sodium supplement agent Na 2 C 2 O 4 , inorganic additive NaNO 2 , conductive agent Super P and binder PVDF in a mass ratio of 35:5:40:20, dissolve them in NMP solvent, and stir under vacuum to obtain a uniform positive electrode slurry. Coat the positive electrode slurry evenly on the aluminum foil current collector and dry it at 80 °C under vacuum to obtain a positive electrode sheet.

[0032] Assemble the obtained positive electrode sheet with a sodium sheet into a half cell, with a Na 2 C 2 O 4 loading of about 1.5 mg cm -2 , and perform constant current charge-discharge tests in the voltage range of 2.0 V - 4.0 V at a current density of 10 mAg -1 . Figure 1 (Solid line) is the first charge-discharge curve of the positive electrode sheet used in Example 1. Electrochemical tests show that the charging curve of the half cell containing the NaNO 2 additive exhibits two platforms (3.25 V and 3.68 V), corresponding to the oxidation decomposition of NO 2 - to NO 2 and the oxidation of Na 2 by NO 2 C 2 O 4 decomposition process, indicating that the NaNO 2 additive significantly reduces the decomposition potential of the Na 2 C 2 O 4 sodium supplement agent. The first charge and discharge capacities are 256.6 mAh g -1 and 8.7 mAh g -1 respectively, and this reaction process is irreversible, indicating that Na 2 C 2 O 4The sodium supplement decomposes completely and releases sodium ions during the first charging process, and does not participate in the reaction during subsequent cycles.

[0033] Comparative Example 1

[0034] The organic sodium supplement Na 2 C 2 O 4 、conductive agent Super P and binder PVDF were mixed evenly in a mass ratio of 40:40:20, dissolved in NMP solvent, and stirred under vacuum to obtain a uniform positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum foil current collector and dried at 80 °C under vacuum to obtain a positive electrode sheet.

[0035] The positive electrode sheet obtained above was assembled with a sodium sheet into a half-cell, with the Na 2 C 2 O 4 loading ~1.5 mg cm -2 At a current density of 10 mA g -1 a constant current charge-discharge test was carried out in the voltage range of 2.0 V - 4.0 V. Figure 1 (Dashed line) is the first cycle charge-discharge curve of the positive electrode sheet used in Comparative Example 1. Electrochemical tests showed that the Na 2 C 2 O 4 half-cell had no plateau in the charging curve, and the first charge-discharge capacity was 0 mAh g -1 , indicating that the decomposition potential of pure Na 2 C 2 O 4 sodium supplement was higher than 4 V, so it could not decompose during the first charging process.

[0036] Example 2

[0037] The positive electrode active material O3-Na 0.9 Ni 0.32 Zn 0.08 Fe 0.1 Mn 0.3 Ti 0.2 O 2 (ZT-NFM), organic sodium supplement Na 2 C 2 O 4 , inorganic additive NaNO 2 , conductive agent Super P and binder PVDF were mixed evenly in a mass ratio of 72:5:3:10:10, dissolved in NMP solvent, and stirred under vacuum to obtain a uniform positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum foil current collector and dried at 80 °C under vacuum to obtain a positive electrode sheet.

[0038] The obtained positive electrode sheet was assembled with a sodium sheet into a half-cell, and the loading of the positive active material (ZT-NFM) was ~1.5 mg cm -2 , and a constant current charge-discharge test was carried out in the voltage range of 2.0 V - 4.0 V at a current density of 10 mA g -1 . Figure 2 (Solid line) is the first-cycle charge-discharge curve of the positive electrode sheet used in Example 2. Electrochemical tests showed that the half-cell of the sodium supplement agent containing NaNO 2 additive and Na 2 C 2 O 4 showed two charge platforms (3.27 V and 3.75 V), corresponding to the processes of NO 2 - oxidative decomposition into NO 2 and NO 2 oxidizing Na 2 C 2 O 4 decomposition, indicating that the NaNO 2 additive significantly reduced the decomposition potential of the Na 2 C 2 O 4 sodium supplement agent; meanwhile, the charge platform introduced with the ZT-NFM positive electrode (high mass ratio) was basically the same as that in Example 1, indicating that the oxidation of NO 2 gas could better overcome the problem of poor conductivity, and then realize the full decomposition of the Na 2 C 2 O 4 sodium supplement agent. The first charge-discharge capacities were 290.2 mAh g -1 and 131.7 mAh g -1 , indicating that the Na 2 C 2 O 4 sodium supplement agent achieved good decomposition during the first charging process without affecting the discharge curve and capacity.

[0039] Comparative Example 2

[0040] The positive active material ZT-NFM, conductive agent Super P and binder PVDF were mixed evenly in a mass ratio of 80:10:10, dissolved in NMP solvent, and vacuum stirred to obtain a uniform positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum foil current collector and dried at 80 °C under vacuum to obtain a positive electrode sheet.

[0041] The obtained positive electrode sheet was assembled with a sodium sheet into a half-cell, and the loading of the positive active material (ZT-NFM) was ~1.5 mg cm -2 , and a constant current charge-discharge test was carried out in the voltage range of 2.0 V - 4.0 V at a current density of 10 mA g -1 .Figure 2 (Dashed line) is the first charge-discharge curve of the positive electrode sheet used in Comparative Example 2. Electrochemical tests show that the first charge and discharge capacities of the ZT-NFM half-cell are 136.0 mAh g -1 and 131.3 mAh g -1 .

[0042] Example 3

[0043] Mix the positive active material ZT-NFM, organic sodium supplement Na 2 C 2 O 4 , inorganic additive NaNO 2 , conductive agent Super P and binder PVDF evenly at a mass ratio of 72:5:3:10:10, dissolve in NMP solvent, and stir under vacuum to obtain a uniform positive electrode slurry. Coat the positive electrode slurry evenly on the aluminum foil current collector and dry it at 80 °C under vacuum to obtain the positive electrode sheet.

[0044] Match the positive electrode sheet obtained above with a hard carbon negative electrode to assemble a full cell. The loading of the positive active material (ZT-NFM) is ~1.5 mg cm -2 , the N / P ratio is 1.05 - 1.10, and perform constant current charge-discharge tests in the voltage range of 1.9 V - 3.9 V at a current density of 10 mAg -1 . Figure 3 (Solid line) is the first charge-discharge curve of the full cell of the positive electrode sheet and hard carbon negative electrode used in Example 3. Electrochemical tests show that the charge curve of the full cell containing NaNO 2 additive and Na 2 C 2 O 4 sodium supplement shows two platforms (3.10 V and 3.70 V), corresponding to the oxidation decomposition of NO 2 - to NO 2 and the oxidation of NO 2 to Na 2 C 2 O 4 decomposition process, indicating that the NaNO 2 additive significantly reduces the decomposition potential of Na 2 C 2 O 4 sodium supplement; at the same time, the charge platform of the ZT-NFM positive electrode / / hard carbon full cell is basically the same as that of Example 2, indicating that NO 2 gas oxidation is universal in half-cells and full-cells, and can better overcome the problem of poor conductivity, thereby realizing Na 2 C 2 O 4The sodium supplement agent is fully decomposed. The initial charge and discharge capacities are 322.5 mAh g -1 and 132.0 mAh g -1 , indicating that Na 2 C 2 O 4 The sodium supplement agent achieved good decomposition during the first charge and compensated for the discharge capacity, and the results showed that Na 2 C 2 O 4 The sodium ions released by the sodium supplement agent made up for the sodium loss in forming SEI on the hard carbon negative electrode side.

[0045] Comparative Example 3

[0046] The positive active material ZT-NFM, the conductive agent Super P and the binder PVDF were mixed evenly in a mass ratio of 80:10:10, dissolved in the NMP solvent, and vacuum stirred to obtain a uniform positive electrode paste. The positive electrode paste was evenly coated on the aluminum foil current collector and dried at 80 °C under vacuum to obtain the positive electrode sheet.

[0047] The obtained positive electrode sheet was assembled with the hard carbon negative electrode to form a full cell. The loading of the positive active material (ZT-NFM) was ~1.5 mg cm -2 , the N / P ratio was 1.05 - 1.10, and constant current charge and discharge tests were carried out in the voltage range of 1.9 V - 3.9 V at a current density of 10 mA g -1 . Figure 3 (Dotted line) is the first cycle charge and discharge curve of the full cell composed of the positive electrode sheet and the hard carbon negative electrode used in Comparative Example 3. Electrochemical tests showed that the initial charge and discharge capacities of the ZT-NFM full cell were 131.9 mAh g -1 and 85.0 mAh g -1 , indicating that the addition of no sodium supplement agent showed a lower discharge capacity due to the sodium loss in forming SEI on the hard carbon negative electrode side.

[0048] Comparative Example 4

[0049] The positive active material ZT-NFM, the organic sodium supplement agent Na 2 C 2 O 4 , the inorganic additive NaNO 2 , the conductive agent Super P and the binder PVDF were mixed evenly in a mass ratio of 70:7:3:10:10, dissolved in the NMP solvent, and vacuum stirred to obtain a uniform positive electrode paste. The positive electrode paste was evenly coated on the aluminum foil current collector and dried at 80 °C under vacuum to obtain the positive electrode sheet.

[0050] The obtained positive electrode sheet was assembled with the hard carbon negative electrode to form a full cell. The loading of the positive active material (ZT-NFM) was ~1.5 mg cm -2, with an N / P ratio of 1.05 - 1.10, at a current density of 10 mA g -1 a constant current charge-discharge test was carried out in the voltage range of 1.9 V - 3.9 V. Figure 4 Figure 4 is the first charge-discharge curve of the full cell composed of the positive electrode sheet and hard carbon negative electrode used in Comparative Example 4. Electrochemical tests show that the full cell containing NaNO 2 additive and Na 2 C 2 O 4 The first charge and discharge capacities of the sodium supplement agent full cell are 431.2 mAh g -1 and 110.2 mAh g -1 respectively, indicating that 7 wt% of Na 2 C 2 O 4 sodium supplement agent is fully decomposed to show a relatively high capacity; however, the discharge capacity is relatively low, which may be due to a large amount of gas generated inside the battery affecting the battery performance.

[0051] Comparative Example 5

[0052] The positive electrode active material ZT-NFM, organic sodium supplement agent Na 2 C 2 O 4 , inorganic additive NaNO 2 , conductive agent Super P and binder PVDF were mixed evenly in a mass ratio of 74:5:1:10:10, dissolved in NMP solvent, and vacuum stirred to obtain a uniform positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum foil current collector and dried at 80 °C under vacuum to obtain a positive electrode sheet.

[0053] The obtained positive electrode sheet was assembled with a hard carbon negative electrode to form a full cell. The loading of the positive electrode active material (ZT-NFM) was ~1.5 mg cm -2 , with an N / P ratio of 1.05 - 1.10, at a current density of 10 mA g -1 a constant current charge-discharge test was carried out in the voltage range of 1.9 V - 3.9 V. Figure 5 Figure 5 is the first charge-discharge curve of the full cell composed of the positive electrode sheet and hard carbon negative electrode used in Comparative Example 5. Electrochemical tests show that the full cell containing NaNO 2 additive and Na 2 C 2 O 4 The first charge and discharge capacities of the sodium supplement agent full cell are 240.4 mAh g -1 and 113.2 mAh g -1 respectively, indicating that NO formed by the oxidative decomposition of 1 wt% NaNO 2 additive 2 cannot oxidize Na 2 C 2 O4 The sodium supplement decomposes completely and cannot make up for the sodium loss caused by the formation of SEI on the hard carbon negative electrode side.

[0054] In summary, by using the inorganic additive NaNO 2 and the organic sodium supplement Na 2 C 2 O 4 The method of pre-sodiation for sodium-ion batteries has remarkable effects. The NO 2 - gas generated by the oxidative decomposition at low potential effectively reduces the decomposition potential of Na 2 due to the reversible reaction of 2 C 2 O 4 and the fact that the gas oxidant can be in full contact with the organic sodium supplement. Meanwhile, after the first charge ends, the NaNO additive and the Na 2 additive and the Na 2 C 2 O 4 sodium supplement exist in the form of gas. The gas can be discharged and then the battery can be sealed again after the formation process, which has no impact on the subsequent electrochemical performance of the material. The ZT-NFM cathode material obtained by this method has a high first-week efficiency and stable cycling performance. In addition, the entire pre-sodiation and gas exhaust process can be compatible with the existing processes, without the need for additional equipment or complex adjustments, and has broad research prospects and application values.

[0055] The specific embodiments described above further elaborate on the purpose, technical solutions, and beneficial effects of the present invention. It should be understood that the above description is only the specific embodiments of the present invention and is not used to limit the protection scope of the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention.

Claims

1. A sodium supplement additive, characterized in that: include: An organic sodium supplement and an inorganic additive, wherein the inorganic additive is a gas-generating sodium salt, and the gas product of the gas-generating sodium salt, when oxidized and decomposed at a certain potential, is oxidizing and can oxidize the organic sodium supplement to decompose and thus realize sodium compensation.

2. The sodium supplement additive according to claim 1, characterized in that The organic sodium supplement is Na2C2O4, and the gas generating sodium salt is NaNO2.

3. The sodium supplement additive according to claim 2, characterized in that The oxidative decomposition potential of the gas-generating sodium salt is 3.0-3.5 V, and the decomposition product is the oxidative gas NO2.

4. A positive electrode sheet, characterized in that: The positive electrode slurry is coated on the surface of the current collector, and the raw materials for preparing the positive electrode slurry include the sodium supplement additive, conductive agent, binder and solvent described in any one of claims 1 to 3.

5. The positive electrode sheet according to claim 4, characterized in that: The mass ratio of the sodium supplement additive, the conductive agent and the binder is 40-50:30-40:10-20.

6. The positive electrode sheet according to claim 4, characterized in that: It also includes positive electrode active material, wherein the mass ratio of the positive electrode active material, sodium supplement additive, conductive agent and binder is 65-75:5-15:10-15:10-15, the organic sodium supplement agent accounts for 3-6% of the mass of the positive electrode slurry, and the inorganic additive accounts for 2-5% of the mass of the positive electrode slurry.

7. The positive electrode sheet according to claim 6, characterized in that: The positive electrode active material is at least one of transition metal layered oxides, tunnel phase oxides, and polyanions.

8. A sodium ion battery, characterized in that: The invention comprises the positive electrode sheet as described in any one of claims 4 to 7.

9. The sodium ion battery according to claim 8, characterized in that: The preparation raw materials also include an electrolyte, a negative electrode plate and a separator. The electrolyte solute is 1M NaPF6, and the solvents are EMC, EC and DMC. The volume ratio of EMC, EC and DMC is 1:1:

1.

10. The sodium ion battery according to claim 9, characterized in that: The negative electrode plate is at least one of a metal sodium plate and hard carbon.

Citation Information

Patent Citations

  • Sodium-ion battery positive plate, preparation method thereof and sodium-ion battery

    CN112768699A

  • Positive plate, preparation method of positive plate, battery, preparation method of battery and electric equipment

    CN118039807A

  • Sodium ion battery positive electrode, preparation method thereof and battery

    CN118538861A

  • Positive pole piece, battery monomer, battery and electric device

    CN119153619A

  • Sodium-ion battery, battery module, battery pack, and electric device

    WO2025020461A1

Cited By

  • Core-shell structure sodium ion battery positive electrode material and in-situ coating preparation method thereof

    CN121366885A

  • A core-shell structure sodium ion battery positive electrode material and an in-situ coating preparation method thereof

    CN121366885B

  • Sodium supplement additive, positive pole piece and sodium ion battery

    CN121484253A